PENGARUH PROFITABILITAS, INVESTMENT OPPORTUNITY SET, DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DIVIDEN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016) - Puteri Prihatini; Dessi Susanti (Jurnal Ecogen, 2018)
The purpose of this study is to analyze the influence of profitability, investment opportunity set, and managerial ownership on dividend policy. The population of this study consists of whole manufacturing companies that listed on Indonesian Stock Exchange (IDX) from 2013 to 2016 by using secondary data. The data have been collected from financial report of companies from Indonesian Stock Exchange (IDX) website and Indonesian Capital Market Directory (ICMD). In this study, the samples are obtained 21 companies out of 145 companies. Analytical method that is used is multiple regression analysis. The hypothesis is measured by using statistical t-test with α level of 5%. The results indicate that profitability gives negative effect but does not significant on dividend  policy of manufacturing companies that listed on Indonesian Stock Exchange (IDX). Meanwhile, investment opportunity set and managerial ownership give positive effect and also significant on dividend policy of manufacturing companies that listed on Indonesian Stock Exchange (IDX).Keyword: profitability, investment opportunity set, managerial ownership, and dividend policy